2022
DOI: 10.1108/bfj-03-2022-0196
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes and sociodemographic profiles in purchasing organic food products: evidence from a Greek and Swedish survey

Abstract: PurposeThis study explores Greek and Swedish consumers' attitude towards organic food consumption in order to demonstrate possible differences that can be identified based on health and ecological consciousness beliefs rather than demographic factors. The examination of an emerging and a more mature market allow the authors to provide more targeted marketing strategies that possibly increase organic food consumption in both countries.Design/methodology/approachThe authors adopt an econometric approach to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Our findings suggest that consumers involved in purchasing organic food could be motivated by the environmental impact of their food choices. Indeed, environmental concern is one of the major motivation factors for organic consumers (Diagourtas et al. , 2023) in countries with a developed and mature organic food market and has proven influencing consumers' willingness to pay for organic foods (Katt and Meixner, 2020) and consumers' purchase intention towards organic food (Eberle et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that consumers involved in purchasing organic food could be motivated by the environmental impact of their food choices. Indeed, environmental concern is one of the major motivation factors for organic consumers (Diagourtas et al. , 2023) in countries with a developed and mature organic food market and has proven influencing consumers' willingness to pay for organic foods (Katt and Meixner, 2020) and consumers' purchase intention towards organic food (Eberle et al.…”
Section: Discussionmentioning
confidence: 99%
“…Views on the definition of a suitable process to be used by each cluster Our findings suggest that consumers involved in purchasing organic food could be motivated by the environmental impact of their food choices. Indeed, environmental concern is one of the major motivation factors for organic consumers (Diagourtas et al, 2023) in countries with a developed and mature organic food market and has proven influencing consumers' willingness to pay for organic foods (Katt and Meixner, 2020) and consumers' purchase intention towards organic food (Eberle et al, 2022). Furthermore, positive environmental beliefs relating to organic products have also been observed in exploratory consumer research (Danner and Menapace, 2020).…”
Section: Consumers View On Communication Of Careful Processingmentioning
confidence: 99%
“…For example, organic food protects the environment, avoids using chemicals and pesticides and is more nutritious than non-organic food. During the COVID-19 pandemic, the demand for organic food increased worldwide (Chetioui et al ., 2022; Diagourtas et al ., 2022; Wojciechowska-Solis and Śmiglak-Krajewska, 2022). Consumers, organizations and academicians paid more focus to organic food (Carrión Bósquez et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The argument is supported by Čolović and Mitić (2022) that organic food still covers a smaller portion of the market and various countries increase sales of organic food. Customer's rapidly increase their consumption of organic food (Diagourtas et al ., 2022). In 2016, global sales of organic food reached USD 90 billion.…”
Section: Introductionmentioning
confidence: 99%
“…The factors influencing the consumption of organic food have been studied extensively. In addition, among the factors that may affect the organic purchasing behavior of people, studies have reported the following factors as vital: the purchasing intention of consumers toward organic food (Kabir and Islam, 2021; Leonidou et al ., 2022; Pham et al ., 2018; Shamsi et al ., 2020), consumer attitude (Diagourtas et al ., 2022; Kumar et al ., 2023; Lavuri, 2022), health orientation (Ditlevsen et al ., 2019; Kirmani et al ., 2022), environmental orientation (Fernandes and Saraiva, 2022; Nosi et al ., 2020), subjective norms (Khan et al ., 2022; Sadiq et al ., 2021), organic cognition (Hu and Meng, 2023; Liu and Zheng, 2019), food safety concerns (Khan et al ., 2023; Le-Anh and Nguyen-To, 2020; Tleis et al ., 2017), consumer value (Cao et al ., 2022; Roh et al ., 2022) and the available media information (Liu et al ., 2021; Pham et al ., 2018; Zheng and Cao, 2022). In particular, organic purchase intention is regarded to be the most vital factor in the prediction of purchase behavior (Leonidou et al ., 2022; Shamsi et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%